Optimization of Movement: A Dynamical Systems Approach to Movement Systems as Emergent Phenomena. Issue 1 (17th October 2018) - Guccione, Andrew A; Neville, Brian T; George, Steven Z
Abstract: The term "movement system" has been defined as "represent(ing) the collection of systems (cardiovascular, pulmonary, endocrine, integumentary, nervous, and musculoskeletal) that interact to move the body or its component parts." 5 Although we do not dispute the advantage of defining the "movement system" as a physiological system, we contend that how the profession is identified with a monolithic "movement system" is imprudent. We contend that our scientific expertise regarding "movement optimization" should move forward by reconsidering how movement is produced (and potentially optimized) as a behavioral phenomenon in itself and abandon further attempts to promote "the movement system" with a purportedly unique and static label. We believe that reframing diagnosis is possible if there is a move away from an exclusive emphasis on classification of anatomical and physiological deviations from "normal" based on organismic constraints when such data yield, at best, an incomplete insight into functional performance that includes environmental and task constraints. The recent application of complex systems approaches to disciplines as diverse as medicine, biology, economics, and meteorology warrants thoughtful consideration of the potential benefits of incorporating similar advances in conceptualization of the central questions in physical therapy.